Erosion Behavior of SKD11 Tool Steel Under Different Impact Angles and Particle Velocities: A Finite Element Analysis Study - Deva Ihsan Khoirunas; Purba, Riki Hendra; Situmorang, Riky Stepanus; James Julian; Fitri Wahyuni; Elvi Armadani; Fathin Muhammad Mardhudhu (DINAMIS, 2025)
The study utilizes the Single Particle Finite Element Analysis (FEA) method with a Cowper-Symonds Strain Rate Material Model to understand the response of SKD11 tool steel to erosion under varying impact angles and velocities. In this study, SiO₂ particles measuring 0.7 mm in diameter were selected as the erodent, while the target material, SKD11, was sized at 1x1x0,5 mm. The impact angle was varied at 30, 60, and 90 degrees, and the impact velocity was set at 25 and 50 m/s. The simulation results show that SKD11 performs best at lower impact angles. It was observed that as the impact angle increases, the erosion also increases significantly, particularly at 60 degrees. Different impact angles also resulted in different erosion mechanisms on the material's surface. The impact velocity further contributed to an increase in erosion, with material failure and material reduction occurring at 50 m/s.